2009
DOI: 10.1111/j.1365-2052.2009.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DGAT1 and GHR on milk yield and milk composition in the Chinese dairy population

Abstract: Previous studies have demonstrated that the p.Lys232Ala substitution in the acylCoA: diacylglycerol acyltransferase (DGAT1) gene and the p.Phe279Tyr mutation in the growth hormone receptor (GHR) gene are the causative quantitative trait loci underlying milk yield and composition on BTA14 and BTA20 respectively. To examine their applications in the genetic improvement of Chinese dairy cattle productivity, we herein investigated the effects of the DGAT1 p.Lys232Ala and GHR p.Phe279Tyr mutations on milk, fat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 11 publications
4
26
1
1
Order By: Relevance
“…This result is consistent with those of previous studies of different breeds, including UK Holsteins (Banos et al, 2008), German Holsteins (Kaupe et al, 2004), Polish Holsteins (Nowacka-Woszuk et al, 2008), and Chinese Holsteins (Sun et al, 2009).…”
Section: Alleles Genotypes and Composite Genotype Frequencysupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with those of previous studies of different breeds, including UK Holsteins (Banos et al, 2008), German Holsteins (Kaupe et al, 2004), Polish Holsteins (Nowacka-Woszuk et al, 2008), and Chinese Holsteins (Sun et al, 2009).…”
Section: Alleles Genotypes and Composite Genotype Frequencysupporting
confidence: 93%
“…However, the GH gene showed no significant effect on any and was not included in the analysis. According to previous studies (Ikonen et al, 2001;Boettcher et al, 2004;Comin et al, 2008;Sun et al, 2009), inconsistent effects, both positive and negative, have been detected depending on the breed or line of dairy cattle. If the studies were conducted using different breeds or lines of dairy cattle, different genetic structures and epistasis effects may have been observed.…”
Section: Effects Of a Single Gene On Milk Production And Milk Composimentioning
confidence: 99%
“…According to the results, milk fat in the milk from the cattle with high allele frequency is meaningfully higher than the milk from the cattle with the low allele frequency. Sun et al [13] have pointed out that the "K" allele of the DGAT1 gene increases the fat concentration of the milk but reduces the milk productivity. However, our findings in milk productivity parameter are not in parallel with Sun et al's findings.…”
Section: Discussionmentioning
confidence: 99%
“…The missense p.Phe279Tyr mutation is one of the most promising markers to improve protein content and milk yield (Sun et al, 2009). Other studies reported the effect of this polymorphism on feed intake, feed conversion, and traits related to energy balance (Banos et al, 2008).…”
Section: Discussionmentioning
confidence: 99%